Protocol to identify a topological superconducting phase in a three-terminal device - Pikulin, Dmitry; van Heck, Bernard; Karzig, Torsten; A. Martinez, Esteban; Nijholt, Bas; Laeven, Tom; Winkler, Georg Wolfgang; Watson, John; Heedt, Sebastian; Temurhan, Mine; Svidenko, Vicky; Lutchyn, Roman; et al. (arXiv, 2021)
We develop a protocol to determine the presence and extent of a topological phase with Majorana zero modes in a hybrid superconductor-semiconductor device. The protocol is based on conductance measurements in a three-terminal device with two normal leads and one superconducting lead. A radio-frequency technique acts as a proxy for the measurement of local conductance, allowing a rapid, systematic scan of the large experimental phase space of the device. Majorana zero modes cause zero bias conductance peaks at each end of the wire, so we identify promising regions of the phase space by filtering for this condition. To validate the presence of a topological phase, a subsequent measurement of the non-local conductance in these regions is used to detect a topological transition via the closing and reopening of the bulk energy gap. We define data analysis routines that allow for an automated and unbiased execution of the protocol. Our protocol is designed to screen out false positives, especially trivial Andreev bound states that mimic Majorana zero modes in local conductance. We apply the protocol to several examples of simulated data illustrating the detection of topological phases and the screening of false positives.